Some New Postquantum Integral Inequalities - Yu-Ming Chu; Muhammad Uzair Awan; Sadia Talib; Sabah Iftikhar; Latifa Riahi (Journal of Mathematics)
The goal of this paper is to derive a new generalized postquantum integral identity. Using this new identity as an auxiliary result, we derive some new variants of integral inequalities using p,q-differentiable preinvex functions. We also point out some special cases of the obtained results which show that our results are quite unifying ones.